NURSING CARE FOR PREVENTING PRESSURE INJURIES IN INTENSIVE CARE UNITS: AN INTEGRATIVE LITERATURE REVIEW. - de Almeida, José Macedo; de Sousa Júnior, Belarmino Santos; da Silva Brandão, Bárbara Maria Lopes; Negromonte Gonçalves, Karyne Kirley; Bezerra, Thaíse Alves (Enfermagem Atual in Derme)
Objective: To describe nursing care for preventing pressure injuries in intensive care units. Methods: This is an integrative literature review, conducted by cross-referencing standardized descriptors using the Health Sciences Descriptors/Medical Subject Headings in scientific databases such as the Scientific Electronic Library Online, Cumulative Index to Nursing and Allied Health Literature, and the Cochrane Library. The review was conducted between November 2024 and March 2025. Results: The application of scales, such as Braden and the Escala de Valoración Actual del Riesgo de desarrollar Úlceras por presión en Cuidados Intensivos (EVARUCI), frequent repositioning, skin hydration, the use of support surfaces and training of the nursing team were highlighted as essential nursing care for injury prevention. Conclusion: Nursing is essential for preventing pressure injuries, highlighting the importance of continuing education, constant monitoring, and the implementation of institutional protocols to ensure safe and effective care.